Institutionalization of integrated community case management into national health systems in low- and middle-income countries: a scoping review of the literature. Issue 1 (1st January 2019) - Nanyonjo, Agnes; Counihan, Helen; Siduda, Sam Gudoi; Belay, Kassahun; Sebikaari, Gloria; Tibenderana, James
ABSTRACT: Background : Integrated community case management (iCCM) for malaria, pneumonia and diarrhea continues to be a recommended strategy to address child mortality in areas where access to health facilities is limited. Objective : To identify models of, and gaps in, institutionalization of benchmark components of iCCM into national health systems of low-and-middle-income countries, in order to draw lessons for future iCCM implementation and sustainability. Methods : A scoping review of relevant searchable policy documents and publications available in English literature was undertaken. Data were selected, collated and characterized by three reviewers using the Arksey and O'Malley framework. Results : Overall 19 countries were reviewed. Despite the existence of discrete policies, most iCCM programs relied heavily on implementing partners and donor financing. Parallel implementing partner-run systems were often used to procure and supply iCCM medicines. These modes of implementation occasionally violated some health system strengthening principles. Drug stock-outs were still prominent in several countries, and iCCM indicators were sometimes not integrated into the national health management information system. There were no clearly defined motivation packages for both salaried and unsalaried workers, and there were several supervision challenges. Community-based performance-financing, use of technology with mobile devices (mHealth), small procedural improvements, and provision of targeted rather than universal services, were some of the promising interventions for improved iCCM institutionalization. Conclusion : Sustainable iCCM will require improved ownership by the benefiting communities and the local and central governments. Government commitment should be evident in budgeting processes and implementation strategies.